Investigação de adulterantes em suplementos alimentares por cromatografia de troca iônica com detecção condutométrica - Dal Molin, Thaís Ramos (2016)
With the increase in the number of regulars gym, concomitantly increases the search for fast and effectives results through the consumption of ergogenic products and food supplements. The dietary supplements are products suitable for athletes, in order to replenish nutrients and other substances lost over the intense physical activities, or else to supplement a diet when this is insufficient. In Brazil, there is no official legislation for dietary supplements, and many times the same product can be regulated by more than one resolution. Because fo the popularization of these products, associated to strong commercial appeal that they are able to modify the physical form, or promotes the weight loss, the manufactures seek to draw consumers’ attention by adding substances that are not allowed in foods. Deliberated adulteration occurs when medicinal drugs are added proposal in order to induce the false impression that the product really works. The pharmaceuticals class commonly describes in the literature used as adulterants are the appetite supressants, diuretics and laxatives, and in this work represented for the sibutramine, amfepramone, femproporex, amiloride and bisacodyl. All these drugs have serious side effects, that when administrated in excess can bring from dehydration with electrolyte loss and even irreversible damages for the organism, such as Cerebrovascular Accident (CVA) and Acute Myocardial Infarction (AMI). As a result, we seek to rapid analytical methodologies, efficient and selective in order to investigate and prevent the possible adulterations in dietary supplements. Ion Exchange Chromatography with Conductivity Detection (IEC-CD) consisted in the electrostatic interaction between the interest analytes and binding sites of the column, combined with a universal detector. Thus, this work aimed to the optimization, validation and application of a screening method for the investigation of the presence of amfepramone, femproporex, sibutramine, bisacodyl and amiloride in dietary supplements samples obtained from Brazilian website. The method was development with a cation exchange column Metrosep C4 100/4.0. The mobile phase consisted of 1.8 mM HNO3 containing 2% of acetonitrile, with flow rate of 0.9 mL.min-1, and conductivity detection without suppression. The limits of detection (LOD) varied from 1.01 until 3.62 mg.mL-1, whereas the limits of quantification (LOQ) were in the range of 1.48 to 8.72 mg.mL-1. The proposal method was applied in 78 solids samples of dietary supplements, and two were suspected of adulteration. One sample showed 9.877 ± 0.05 mg.g-1 of sibutramine, and another 8.076 ± 0.01 mg.g-1 of bisacodyl. The method presented be linear, specific, selective and applicable for large number of samples. The possible presence of these adulterants suggests more investigations about the real information describes on the labels of dietary supplements, pre-market safety and efficacy tests and the requirement of commitment from manufactures with the current legislation.